Faktor – Faktor yang Mempengaruhi Purchase Intention - Musfira, Liana; Astuti, Budi (SAFE-Network, 2024)
With the increasingly advanced development of the internet, many people are purchasing goods online. People's increasing purchasing intentions indicate consumptive behavior. This is supported by the rise of platforms on social media that present a wide selection of goods. One of them is TikTok which is full of offers and promotions that make TikTok users interested in making purchases. This research aims to analyze the influence of perceived ease of use, perceived usefulness, structural assurance, social influence, and intimacy on purchase intention. The population in this study are users of the TikTok application in Indonesia. The samples in this study were taken using purposive sampling techniques and questionnaire methods and obtained 170 samples that met the convenience sampling criteria. This research uses data processing software SPSS version 26. The research results show that perceived ease of use, perceived usefulness, structural assurance, social influence, influence purchase intention. Meanwhile, intimacy has no effect on purchase intention.